KESATUAN (KESIAPAN TNI AL SIMEULUE DALAM MENCEGAH ILLEGAL, UNREPORTED, UNREGULATED FISHING) - Balqis Fahira Ninggrum; Ayu Wulandari; Neli Ria Rifanda; Nodi Marefanda (Jurnal Public Policy, 2018)
This study aims to analyze the readiness of the Navy of Simeulue in preventing illegal, unreported, unregulated (IUU) fishing and want to know what are the supporting factors and obstacles for TNI AL Simeulue in preventing IUU fishing. This study uses a qualitative method with a descriptive approach. Data retrieval is done by observation, interview and documentation techniques. The results showed that the readiness of AL Simeulue in preventing illegal, unreported, unregulated with various indicators, namely physical, mental, needs and knowledge conditions had fulfilled two indicators, namely physical and mental conditions. While the needs and knowledge cannot be said to be good. A supporting factor for the Navy of Simeulue in preventing IUU Fishing is the establishment of good coordination between the Simeulue Navy Post which is under Lanal Simeulue and the cooperation that has been established with other related agencies. In addition there are also obstacles to the Indonesian Navy's AL Simeulue in preventing IUU Fishing, namely the lack of facilities and infrastructure as well as weak coordination between the various agencies involved and can lead to overlapping of their respective authorities and policies, so it is very vulnerable to conflict of interests.Keywords: IUU Fishing, Readiness, Indonesian Navy Simeulue